(untitled) (Editora Impacto Científico, 2025)
Cognitive Neuroscience as an unfolding of one of the five areas of Neuroscience can, based on the analysis of human behavior, establish a relationship with education, the central area of ​​this study, which aims to form a certain society according to its own interests and due to the image that we want to form this society based on the educational system which is established by it. Thus, from a technological perspective, this work uses qualitative bibliographical research on academic materials, intending to first understand the definition of cognitive Neuroscience, education and Technology, and then study the convergence that may exist between the three areas, finally concluding that there is in fact clarity between them, which needs to be admitted and evidence in a moderate way, so that one can understand the benefits that technology can provide both to cognitive neuroscience in the study of behavior, and to education in the exercise of citizenship. DOI: https://doi.org/10.56238/edimpacto2025.090-002